2021
DOI: 10.3389/fphar.2021.700703
|View full text |Cite
|
Sign up to set email alerts
|

A Birds-Eye (Re)View of Acid-Suppression Drugs, COVID-19, and the Highly Variable Literature

Abstract: This Perspective examines a recent surge of information regarding the potential benefits of acid-suppression drugs in the context of COVID-19, with a particular eye on the great variability (and, thus, confusion) that has arisen across the reported findings, at least as regards the popular antacid famotidine. The degree of inconsistency and discordance reflects contradictory conclusions from independent, clinical-based studies that took roughly similar approaches, in terms of both experimental design (retrospe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(74 reference statements)
1
3
0
Order By: Relevance
“…Famotidine, marketed as Pepcid ® , is an FDA approved histamine H2 receptor antagonist prescribed to treat heartburn. Two retrospective studies later conducted in the US also confirmed similar findings ( Freedberg et al, 2020 ; Mather et al, 2020 ), however, like most reports for repurposed drugs, the mechanism of action underlying the observed beneficial effects remain ill-defined ( Mura et al, 2021 ). One computational study suggested Mpro ( Wu C. et al, 2020 ) as the target, while another suggested PLpro ( Kandeel et al, 2020 ).…”
Section: Critical Assessment Of Examples Of Drug Repurposing “Hits”supporting
confidence: 56%
“…Famotidine, marketed as Pepcid ® , is an FDA approved histamine H2 receptor antagonist prescribed to treat heartburn. Two retrospective studies later conducted in the US also confirmed similar findings ( Freedberg et al, 2020 ; Mather et al, 2020 ), however, like most reports for repurposed drugs, the mechanism of action underlying the observed beneficial effects remain ill-defined ( Mura et al, 2021 ). One computational study suggested Mpro ( Wu C. et al, 2020 ) as the target, while another suggested PLpro ( Kandeel et al, 2020 ).…”
Section: Critical Assessment Of Examples Of Drug Repurposing “Hits”supporting
confidence: 56%
“…According to other researchers, this mechanism of action of famotidine as a component of etiotropic therapy is not proven, and the search for real mechanisms of its positive effect should be carried out from the standpoint of pathogenetic therapy, taking into account, first of all, the interaction of famotidine with H2-receptors [ 78 ]. At the same time, discussion of the efficacy of famotidine as an antagonist of H2-receptors often boils down to a discussion of its antacid properties associated with inhibition of the proton pump [ 79 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many putative candidates against SARS-CoV-2 PLpro identified by in silico studies have yet to be biochemically confirmed 13,[28][29][30][31] . Several repurposed protease inhibitors with promising effects on PLpro in vivo or in vitro, such as simeprevir, tanshinones, famotidine, and ebselen, are either clinically ineffective or still in clinical trials [32][33][34][35][36] . Another class of inhibitors of interest against PLpro is FDA-approved zinc-ejecting drugs 15,17,37,38 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous in-silico attempts have been made in repurposing drugs to target SARS-CoV-2 PLpro, but putative drug candidates still remain to be biochemically confirmed (Klemm, Ebert et al 2020, Smith, Davis-Gardner et al 2020, Redhead, Owen et al 2021, Xu, Chen et al 2021, Zhao, Du et al 2021. Meanwhile, several repurposed drug candidates against PLpro have gained traction when tested in-vivo or in-vitro -Simeprivir, Tanshinone, Famotidine and Ebselen, to name a few (Jin, Du et al 2020, Gammeltoft, Zhou et al 2021, Lim, Tan et al 2021, Mura, Preissner et al 2021, https://doi.org/10.21203/rs.3.rs-26344/v1. However, these drug candidates are either found clinically ineffective, are still under clinical trials, or still require thorough biochemical assessment (Calleja, Lessene et al 2022).…”
Section: Introductionmentioning
confidence: 99%